Building Export Competitiveness in Laos : Summary Report - World Bank (World Bank, Washington, DC, 2012)
The basic framework for the background study on building export competitiveness in Laos is based on the National Growth and Poverty Eradication Strategy (NGPES), which appropriately stresses the need to: (i) improve the business climate by creating a predictable and transparent policy environment; (ii) streamline administrative procedures and regulations that are an obstacle to domestic and foreign private investment; and (iii) strengthen market institutions, including most notably those related to dispute resolution and contract enforcement. This paper focuses on three key priority areas: (a) Strengthening fiscal management is a first priority area. Progress in strengthening fiscal management is likely to require reforms to the broader framework of center-province fiscal relations; (b) Establishing a functioning banking system is a second priority area. Laos needs an efficient banking system to achieve the government's development goals and meet the competitive challenges of regional integration; and (3) Improving competitiveness is a third priority area. Conventional macroeconomic assessments of competitiveness using real effective exchange rates do not suggest any major competitiveness concerns. Other approaches, involving a more detailed assessment of the various elements that make up the investment climate, suggest that competitiveness is a major impediment to attracting investment to Laos. This study addresses the main elements of the reform agenda to strengthen Laos' competitiveness, placing special emphasis on trade facilitation and reforms to the business environment.